It-Based Usury Free Financial Innovations - Bidabad, Bijan; Allahyarifard, Mahmoud (American Finance & Banking Review, 2019)
Despite development and extension of different ways of financing in financial markets, encompassing Islamic and conventional financing, the mechanism of Electronic Funds Transfer (EFT) of  project financing both as borrowed and non-borrowed methods has not been considered at most. Moreover overall IT infrastructures development namely Real Gross Settlement System (RTGS), Automatic Clearing House (ACH), Scriptless Security Settlement System (SSSS) and International Bank Account Number (IBAN) for authentication process and the international meta bank network of Single Euro Payment Area (SEPA) and also international integrated banking networks including the Society For Worldwide Interbank Financial Telecommunication (SWIFT) and Interbank Information Transfer Network (Shetab), and other accomplished endeavors are not efficient in absorbing international contributions for project financing through foreign exchange funds in the different countries, satisfactory E-Payment mechanism in informative portal systems for investment projects are weak. In this way, the role of applying E-Payment systems for attracting foreign investment through retail resources mobilization and design of financial instruments with the capability of transacting in the secondary markets should be reconsidered. In this paper by having a glance at different types of investment project financing, we introduce a new project financing mechanism based on E-Payment with non-usury financial instruments to complete investment project financing chain in the form of Rastin Profit and Loss Sharing (PLS) banking.Sharia compliance of financing instruments in one side and accessibility in absorbing international retail foreign exchange sources on other side are two fundamental discussible items in this paper. In this way by designing a new system of "Non-Usury Scriptless Security Settlement System" (NSSSS) with non-usury mechanisms -avoiding legislative (Sharia) circumvention- can provide the two cited goals in designing non-usury financing instruments through IT-based non-usury financial innovations which includes of Rastin Certificates in Rastin PLS banking, and Non-Usury Bonds namely Rastin Swap Bonds.